Crashing from cadaver to computer: Covid‐driven crisis‐mode pedagogy spawns active online substitute for teaching gross anatomy. Issue 5 (3rd September 2021) - Harrell, Kelly M.; McGinn, Melissa J.; Edwards, Cherie D.; Warren Foster, Kenneth; Meredith, M. Alex
Abstract: In early 2020, the Covid‐19 crisis forced medical institutions worldwide to convert quickly to online platforms for content delivery. Although many components of medical education were adaptable to that format, anatomical dissection laboratory lost substantial content in that conversion, including features of active student participation, three‐dimensional spatial relationships of structures, and the perception of texture, variation, and scale. The present study aimed to develop and assess online anatomy laboratory sessions that sought to preserve benefits of the dissection experience for first‐year medical students. The online teaching package was based on a novel form of active videography that emulates eye movement patterns that occur during processes of visual identification, scene analysis, and learning. Using this video‐image library of dissected materials, content was presented through asynchronous narrated laboratory demonstrations and synchronous/active video conference sessions and included a novel, video‐based assessment tool. Data were obtained using summative assessments and a final course evaluation. Test scores for the online practical examination were significantly improved over those for previous in‐person dissection‐based examinations, as evidenced by several measures of performance (Mean: 2015–2019: 82.5%; 2020: 94.9%; P  = 0.003). Concurrently, didactic test scores were slightly, but not significantly, improved (Mean: 2015–2019: 88.0%; 2020: 89.9%). Student evaluations of online sessions and overall course were highly positive. Results indicated that this innovative online teaching package can provide an effective alternative when in‐person dissection laboratory is unavailable. Although this approach consumed considerable faculty time for video editing, further development will include video conference breakout rooms to emulate dissection small‐group teamwork.